2013
DOI: 10.25225/fozo.v62.i4.a8.2013
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the American minkNeovison visonin an agricultural landscape in western Poland

Abstract: Abstract:We studied the diet of the American mink (Neovison vison) in small artificial watercourses located in a farmland area of the valley of the River Barycz in Poland. Rodents, mainly Microtus spp., were the most frequent prey identified, occurring in 88.3 % of all analyzed mink scat. Minks also fed willingly on fish, birds and amphibians, whereas insects, crayfish and reptiles accounted for only a small part of the biomass of food consumed. The food niche breadth of the mink's diet was wide, and varied si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…These watercourses are midfield, highly human‐transformed canals from which riparian vegetation has been removed (detailed description in Krawczyk et al. ). The second study area was located along the Gwda River (53°18′ N, 16°47′ E), which has a semi‐natural character and abundant riparian vegetation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These watercourses are midfield, highly human‐transformed canals from which riparian vegetation has been removed (detailed description in Krawczyk et al. ). The second study area was located along the Gwda River (53°18′ N, 16°47′ E), which has a semi‐natural character and abundant riparian vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…The first study area was located in the Barycz Valley Landscape Park in western Poland (51°34′ N, 17°40′ E) and consisted of five small watercourses in an agricultural landscape. These watercourses are midfield, highly human-transformed canals from which riparian vegetation has been removed (detailed description in Krawczyk et al 2013). The second study area was located along the Gwda River (53°18′ N, 16°47′ E), which has a semi-natural character and abundant riparian vegetation.…”
Section: Diet Analysis: Case Studymentioning
confidence: 99%
“…Подобные результаты изложены A. J. Krawczyk с соавт. [34] при изучении питания норки в Западной Польше, где ракообразные были основой рациона хищника в агрокультурных угодьях. Весной норка пита-ется также млекопитающими (χ 2 = 28.5; df = 4; p < 0.0001) (рыжей полевкой и лесной мышью), которых активно отлавливает в полях и в защит-ных лесополосах.…”
Section: результаты и их обсуждениеunclassified
“…Species identification from faeces in the field can be subjective and uncertain, resulting in high misclassification rates, because it depends on the experience of the observer, the degree of preservation of the faeces, the quantity and quality of associated evidence and the presence of other carnivore species that may deposit similar faeces (Fernández et al , Farrell et al , Davison et al , Chame , Harrington et al ). Despite these limitations, studies based on faeces identified in the field (hereafter referred to as ‘low confidence identification’, LCI) still constitute the main source of knowledge on the diet of many mammalian carnivore species (Fedriani and Fuller , Rodríguez‐Estrella et al , Carrillo et al , De Villa‐Meza et al , Alves‐Costa et al , Rosalino et al , Cunningham et al , Bustamante‐Ho , Krawczyk et al ). In contrast, faeces identification using laboratory methods such as biliary acid and DNA analyses (hereafter ‘high confidence identification’ HCI) have yielded more accurate results (Fernández et al , Kohn and Wayne , Hansen and Jacobsen , Davison et al , Palomares et al , Harrington et al , Roques et al ), but their use is still restricted because they are costly and may require the development of highly specialized, species‐specific laboratory protocols (Cazón‐Narvaez and Sühring , Palomares et al , Roques et al ).…”
mentioning
confidence: 99%